Effects of oxidation defense system exposure to Benzo(a)pyrene on CYP450 gene expression and EROD activity in Crassostrea gigas and Mytilus coruscus. Issue 1 (1st January 2021) - Li, Lei; Ping, Xianyin; Li, Ziniu; Xv, Guodong; Wang, Cuihua; Jiang, Mei
ABSTRACT: Benzo[a]pyrene (BaP) is widely used as a reference compound when studying the toxicity of Polycyclic aromatic hydrocarbons (PAHs) to natural communities. In this study, 15d after exposure to BaP at the nominal concentrations of 5, 1 and 0.2 μg/L, liver, gill and mantle tissues of Crassostrea gigas  and  Mytilus coruscus were taken for BaP uptake assessment, and Cytochrome P450 (CYP450) gene expression level and 7-ethoxyresorufifififin O-deethylase (EROD) activity testing, respectively. CYP450 gene expression level and EROD activity increased significantly with the increase of BaP exposure concentrations. The Significant correlations between BaP uptake and both CYP450 gene expression level and EROD activity indicates that they can be used as a suitable tools for the study of comprehensive levels of biomarker exposed to PAH. There were significant differences in the measurement results of these tissue antioxidant defenses parameters between different treatments.